Integration Policy Implementation in Finland: An emphasis on integration training and development for immigrants - Maggon, Manu (My University, 2015)
Immigrant integration is a term which is used to describe immigrants having same opportunities as natives. For policy makers it is important to measure the condition and situation of immigrants after they arrive in the host country. The research focuses on question like, how immigrants can be integrated. How can immigrant be educated to contribute in development of the society? The main problem is to develop appropriate vocational training program, so that immigrant can come forward to help themselves. This further challenge the authority working with immigrant integration to emphasis on the barriers the immigrant deal with. This study has been approached with the qualitative method. The main methods used here is document analysis and semi-structured interviews. The empirical finding is mostly based on document analysis. This research is based on the provisions provided by the Government in Finland regard to integration of immigrants and protection of asylum-seekers and refugees. However, Finland being part of European Union, EU approach to migration and on the issue of integration has been analyzed as well. Integration is a two-way process between immigrants and society, and there is a need for positive dialogue between all groups in society. Finland Act on Integration of Immigrants aims to provide immigrants access to full participation in all sectors of Finnish society, while maintaining the possibility to keep their own language. Focus areas of Integration Training in Finland is to improve the status of immigrants in labor market, by reducing the unemployment rate in accordance with the Government program. Besides, Integration Training is according to individual need and objective is to ensure that all the immigrants receive more effective access to studying language and social rules.
Keywords: Integration; Integration Training; integration policies; provisions; fi=Julkisjohtaminen|en=Public Management |; fi=Master's Degree Programme in Intercultural Studies in Communication and Administration|